Comparison of one‐step with two‐step production of Bacillus atrophaeus spores for use as bioindicators. Issue 6 (3rd November 2022) - Stier, Philipp; Kulozik, Ulrich
Abstract: The production method of spores significantly influences the resistance of spores used as bioindicators (BI) in the validation of sterilization of packaging material surfaces in aseptic food manufacturing. Therefore, the standardization of the spore production method represents an important and desirable goal in industrial BI production to ensure reliable validation test results. Previously, we recommended a two‐step production approach for submerged spore production, in which the cultivation phase to obtain high cell mass was separate from the sporulation phase. In this work, a one‐step manufacturing process was investigated to reduce production complexity and facilitate standardization of spore production. It was found that one‐step BI production is technically possible but at the expense of spore yield. The two‐step manufacturing process can realize almost 10‐fold higher spore yields. Abstract : The production method of spores significantly influences the resistance of spores used as bioindicators (BI) in the validation of sterilization of packaging material surfaces in aseptic food manufacturing. Therefore, the standardization of the spore production method represents an important and desirable goal in industrial BI production to ensure reliable validation test results. A one‐step manufacturing process was investigated in this work to reduce production complexity. Compared to the recommended two‐step manufacturing process, almost 10‐fold higher yields can be realized.